How Self-Employed Women with Children Manage Multiple Life Roles - Hudson Breen, Rebecca E.; Tasker, Susan L.; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2017)
Although there is a strong body of existing research on women’s career-life development and on women’s entrepreneurship, there is a lack of understanding of the specific experiences of mother entrepreneurs. This grounded theory study addresses the question of how self-employed women with children manage their multiple life roles. The core category “Keeping Going” illustrates a basic social process that is recursively fuelled and affected by 7 key properties: feeling supported, making choices, adapting creatively, remembering the push, remembering the pull, envisioning the future, and living my values. Implications for further research and counselling practice are discussed.